Selected Buildings (1978)
Contiene: Hôtel Jassede 1893 - Hôtel Delfaut c. 1894-95 - Ecole du Sacré- Cœur (now ´Les Colonnes de Guimard´) 1895 - Castel Bérenger 1894-98
Keywords: GUIMARD, HÉCTOR; FRANCIA; PARIS; ARQUITECTURA HOTELERA; HOTELES; CASTILLOS; ARQUITECTURA ESCOLAR; ESCUELAS